Determinan Multifaktorial Readmisi 30 Hari Pada Pasien Gagal Jantung dan Relevansi Temuan Bagi Praktik Keperawatan: Tinjauan Literatur - Regyta Marshanda; Rivani Nur Oktavia; Supadi Supadi (Universitas Pahlawan Tuanku Tambusai, 2026)
Heart failure is a chronic clinical syndrome with increasing global prevalence and remains one of the leading causes of recurrent hospital admissions among adults and older populations. Approximately 20–25% of patients experience readmission within 30 days after hospital discharge. Thirty-day readmission has been widely used as a quality indicator of healthcare services, reflecting the effectiveness of transitional care and continuity of care. Identifying predictors of early readmission is essential to support risk-based nursing interventions. This study aimed to identify and analyze predictors of 30-day readmission in patients with heart failure through a synthesis of recent scientific evidence. This study is a literature review conducted through a systematic article search process. The literature search was performed using Google Scholar via the Publish or Perish application with the keywords “heart failure” AND “30-day readmission” AND (“risk factors” OR predictors), covering publications from 2015 to 2025. Articles that met the inclusion criteria were analyzed qualitatively to identify and compare predictors of 30-day readmission. The 30-day readmission rate ranged from 17% to 28%. Clinical factors and comorbidities were the most dominant predictors, including chronic kidney disease (aOR 1.32), high comorbidity burden (OR 1.45), diabetes mellitus (aOR 1.18), and chronic obstructive pulmonary disease (OR 1.27). Demographic factors such as age <65 years (OR 1.21) and male sex (aOR 1.09) demonstrated more modest associations. Socioeconomic determinants, including low income and public insurance status, increased readmission risk by 10–25%. Risk prediction models showed moderate discriminative ability (AUC 0.60–0.68). Thirty-day readmission in heart failure patients is influenced by multifactorial determinants, with clinical comorbidities playing a dominant role and reinforced by social determinants. Risk-based nursing approaches, including early risk stratification and structured discharge planning, may help reduce readmission rates and improve patient outcomes.